Director independence: Going beyond misaligned incentives to resource dependence. Issue 1 (February 2022) - Hom, Conan; Samson, Danny; Cregan, Christina; Cebon, Peter
Board director independence is critical to achieving and maintaining control to address the agency theory–based issue of interest misalignment between the principal (the organization) and the executives (agent). However, theoretical and empirical research and strategic risk considerations have brought into question the role or relevance that director independence plays in these control task and agency theory domains. We ask, using a quantitative survey method, whether board activity–based applications of independence may be associated with the service task of the board, namely its resource dependence mission. Our findings suggest that the resource dependence duty of the board may be positively associated with some autonomous activities, and yet other activities might be driven primarily by normative practices. Based on this, we suggest that a theoretical scope beyond and greater than agency theory may be needed when reassessing the role of director independence. JEL Classification:M1, O3